2016
DOI: 10.1080/02640414.2016.1252051
|View full text |Cite
|
Sign up to set email alerts
|

Collision count in rugby union: A comparison of micro-technology and video analysis methods

Abstract: The aim of our study was to determine if there is a role for manipulation of g force thresholds acquired via micro-technology for accurately detecting collisions in rugby union. In total, 36 players were recruited from an elite Guinness Pro12 rugby union team. Player movement profiles and collisions were acquired via individual global positioning system (GPS) micro-technology units. Players were assigned to a sub-category of positions in order to determine positional collision demands. The coding of collisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
2
38
1
Order By: Relevance
“…Microsensors and associated algorithms have been used to detect tackles in rugby league 14 with accuracy improving with greater impact forces and longer duration of events. 15 However, this technology has previously been shown to be less useful for detecting tackle events in rugby union 21 and Australian football 42 match-play. A possible explanation for the poor performance of the algorithm in Australian football and rugby union match-play is that the tackle algorithm was trained on rugby league players, to identify rugby league tackles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsensors and associated algorithms have been used to detect tackles in rugby league 14 with accuracy improving with greater impact forces and longer duration of events. 15 However, this technology has previously been shown to be less useful for detecting tackle events in rugby union 21 and Australian football 42 match-play. A possible explanation for the poor performance of the algorithm in Australian football and rugby union match-play is that the tackle algorithm was trained on rugby league players, to identify rugby league tackles.…”
Section: Discussionmentioning
confidence: 99%
“…Of the contact movements performed during regular match-play, scrum events occur around 25 times per game, while depending on playing position, each player will complete approximately 30 rucks and tackles per match. 5,11,[19][20][21] Given the need for more time-efficient and accurate methods of evaluating the incidence and physical demands of contact events in Rugby Union, this research sought to establish the validity of a microsensor-based algorithm for the automatic detection of scrum events during training and match-play. Based on the demonstrated capabilities of inertial devices to quantify other aspects of sports performance, 11,22 it was hypothesised that scrum events could be accurately detected using wearable microsensors.…”
mentioning
confidence: 99%
“…Collisions were not included in this analysis due to current GPS technology's inability to validly quantify collisions in rugby union. 13 Reardon et al 14 have highlighted that current GPS technology under-and overestimates collision count, when compared to video analysis. Accelerations and decelerations were not included in our study, due to reported issues over the validity of quantifying these metrics with current GPS technology.…”
Section: Methodsmentioning
confidence: 99%
“…These authors suggested that the higher g force used to detect collisions from backs compared with forwards was likely due to velocity into contact. 12 A more recently published study has demonstrated a high correlation (0.96) between MST coded and video-coded collision events in rugby league. 13 Player Load™ (Catapult Group International Limited, Melbourne, Australia), and its variants (Player Load™ Slow, Player Load™ 2D) have also been described in the literature as potential indicators of collision or contact loading in rugby codes.…”
Section: Introductionmentioning
confidence: 95%